Analysis of Instagram User Reception Against the Use of Korean Actors as Local Skincare Brand Ambassadors @somethincofficial - Anna Nurjanah; Tiara Indah (Universitas Terbuka, 2022)
The Korean wave phenomenon in Indonesia is marked by the increasing number of people adapting Korean cultures such as food, fashion, and language. Until more and more local Indonesian products use BA K-pop, one of which is skincare brand Somethinc. When examined further, there is a contradiction between the skin color characteristics of Korean actors and the skin color of the majority of Indonesians. This study aims to find out how Instagram users interpret advertisements featuring Han So Hee promoting brightening series products. By using qualitative methods and interpretive paradigms through a reception analysis method approach. This study use interview as data collection techniques. The results of interviews with informants were then grouped into 3 (three) categories, namely Dominant Hegemonic, Negotiated, or Oppositional Position. This study shows the results from 6 sources that there are 2 people included in the Dominant Hegemonic category, then 1 person in the Negotiated category, and 3 people in the Oppositional Position category.